(untitled) (Semiárida, 2025)
In recent decades, with the increase in environmental pollution, the scarcity of natural resources, the problems associated with the climate crisis, and the consequences of these phenomena on societies, concern for environmental issues has become more prominent on the public agenda both in Argentina and internationally. Within this framework, Political Ecology is an intellectual field associated with Environmental Justice movements that understands environmental degradation as a political problem and considers environmental problems to be linked to poverty and the marginalization of certain social sectors. The objective of this review is to develop the potential of Political Ecology, and particularly its proximity dimension, as a perspective for studying urban-environmental conflicts in Latin American cities. This work is theoretical, the methodology employed is descriptive and qualitative, and the research is guided by a bibliographic and documentary review of existing secondary sources on concepts linked to Political Ecology from its emergence in the 1960s and 1970s to the present. The results obtained, based on the theoretical review taking the case of the Metropolitan Area of Buenos Aires to exemplify the concepts developed and the conclusions arrived at, are mainly associated with the understanding of Political Ecology as a current that not only has global scope, but also allows the study of concrete urban-environmental conflicts, at a local scale, making it possible to understand reality and the links between societies and nature in their complexity and multiple dimensions.